Sexually transmitted infections and associated factors during pregnancy in Gondar city, Northwest Ethiopia, 2021: A multicenter study - Nuhamin Tesfa Tsega; Bosena Abebe; Tenaye Ebabu; Tigist Asmare; Mulu Kassa; Tsion Tadesse Haile; Asmra Tesfahun Seyoum; Mastewal Endalew; Kindu Yinges Wondie (Elsevier, 2022)
Background: Sexually transmitted infections are one the most important public health problems in the developing countries that have been reported to have many adverse pregnancy outcomes. Despite the adverse pregnancy outcomes, studies on the prevalence and associated factors of sexual transmitted infection among pregnant women in Ethiopia, especially in our study setting are scarce. Therefore, this study aimed to assess the prevalence and associated factors of sexually transmitted infection among pregnant women in Gondar city, Ethiopia. Methods: An institution-based cross-sectional study was conducted among 507 pregnant women who were attending antenatal care in public health facilities in Gondar city from September 1 to 30, 2021. A systematic random sampling technique was used to select the study participants and data were collected using pretested and interviewer-administered questionnaire. Data were entered using Epi-data version 4.6 and cleaned, and analyzed using SPSS version 25 software. Multivariable logistic regression model was used to determine factors associated with sexual transmitted infection among pregnant women. Adjusted odds ratio (AOR) with 95% of confidence interval and p value < 0.05 were used to declare the significant variables. Results: A total of 507 pregnant women were included in this study, and making a response rate of 97.3%. The prevalence of sexually transmitted infections among pregnant women was 15.2% (95% CI: 12.1%, 18.3%). Being rural resident (AOR = 2.96, 95% CI: 1.43, 6.12), having history of stillbirth (AOR = 2.68, 95% CI: 1.08, 6.68), having history of sexually transmitted infections (AOR = 2.77, 95% CI: 1.10, 7.01) and husbands suspected of having other sexual partners (AOR = 4.73, 95% CI: 2.16, 10.38) were significantly associated with sexually transmitted infections. Conclusion: In this study, sexually transmitted infections were a public health problems because one sixth of pregnant women experienced sexually transmitted infections. Pregnant women with the identified factors need special focus to tackle the problem and its negative health consequences. Moreover, it is better to provide community-based education programmes focusing on changes to sexual behavior for male to tackle this public health important problem.